Reasons for choosing medicine and career suitability among medical students - Khairani Omar,; Mohamed NA,; Ismail Z,; Shalinawati R,; Chamhuri NH,; Rahim NS, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Choosing a course to pursue is an important decision for students to make. A suitable career should correspond to the students’ personalitiy for future work satisfaction and success. The objectives of this study were to determine the students’ reasons for choosing medicine, their personality traits and aptitude (suitability). This was a cross-sectional study involving all third-year medical students at Universiti Sains Islam Malaysia. A self-administered questionnaire was used, which included questions on demographic data, Sidek Career Interest Inventory and reasons for choosing medicine. The inventory was used to measure the students’ personality traits and career suitability. A total of 80 students participated in the study. Majority of them were females (n=56, 70.0%). The findings showed that 45.7% (n=44) of the repondents chose medicine because of ‘passion and interest’, while 24.7% (n=20) and 19.8% (n=16) because of ‘parental influence’ and ‘to help the society’, respectively. For medicine, two personality traits are essential which are investigative and social personality traits. Approximately, 47.5% (n=38) of the respondents had high scores in investigative personality trait. However, only 13.8% (n=11) of them had high scores in social personality trait. Only 12.5% (n=10) of the students had high scores when combining both of the traits. Majority of the students chose medicine for altruistic reasons. However, only a few of them had suitable aptitude for this course namely investigative and social skill. Therefore, the students and the teachers need to be aware of these issues and cultivate the required skills in the students for better career outcome.